Keabsahan Kebijakan Pemerintah Kabupaten Seram Bagian Barat Mengenai Pemilihan Kepala Desa Adat Secara Serentak - Sahertian, Chelsy; Pietersz, Jemmy Jefry; Pattinasarany, Yohanes (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The West Seram Regency Government Makes a Policy Regarding the Simultaneous Election of Village Heads which also involves Traditional Villages whose governance arrangements should be based on intestinal origin rights and local customary law.Purposes of the Research: The purpose of this paper is to analyze the authority of the West Seram Regency Government in making the policy of selecting the traditional village head simultaneously and to analyze the validity of the policy of the West Seram Regency Government to make the simultaneous election of the traditional village head. Methods of the Research: The research method used is normative juridical, the problem approach used in the research is the statutory and conceptual approach. The sources of legal materials used are primary, secondary, and tertiary legal materials. The technique of collecting legal materials carried out in this study was library research, then analyzed using qualitative methods.Results of the Research: Based on the research, the policy carried out by the regional government of the western part of Seram Regency to conduct the election of the traditional village head simultaneously has no validity because the provisions of the legislation do not give the local government the authority to conduct the election of the traditional village head simultaneously. However, when the West Seram Regency Regional Regulation No. 11 of 2019 concerning Villages was stipulated, which in Article 3 caused problems in the customary law community in the West Seram district, because the villages as mentioned in Article 3 by the customary law community were customary villages or Therefore, the actions of the regional government of the West Seram Regency make and stipulate the provisions of Article 3 of Regional Regulation No. 11 of 2014 concerning Villages, which stipulates that 92 customary lands or villages become villages is an act of erasing and not recognizing and respecting the country as a traditional village in the West Seram district, which has received recognition in the provisions of Article 18B paragraph (2) of the 1945 Constitution which regulates that the State recognizes and respects customary law community units and their traditional rights as long as they are still alive and in accordance with the development of society and the principles of the Unitary State of the Republic of Indonesia, which are regulated by law.